การควบคุมการปล่อยแก๊สของการเผาไหม้ถ่านหินและชีวมวลในฟลูอิไดซ์เบดแบบหมุนเวียน - ปิยะพันธ์ จะกอ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
In this research, rice husk was co-firing with coal. Circulating fluidized bed of 0.1 m diameter and 3 m height was built for the combustion. The combustion experiments were carried out with various rice husk ratio (0, 7.02, 13.11, 23.19 %). Moreover, limestone (Ca/S = 0, 0.5, 1, 2, 3 molar ratio) was mixed with coal and rice husk to reduce SO[subscript 2] emission. The effect of rice husk ratio and limestone on flue gas composition (CO[subscript 2], CO, O[subscript 2], NO, NO[subscript 2], SO[subscript 2]) was investigated. Temperature distribution along the riser was also measured. The preliminary results show that the maximum amount of rice husk that can be used was 13.11 %. The emission of NO, NO[subscript 2], and O[subscript 2] increased with increasing rice husk ratio, but CO and SO[subscript 2] show the reverse trend. The temperature at the bottom of the riser also increased when increasing rice husk ratio. About 80.08 % of sulfur was removed by adding limestone at a Ca/S ratio of 3. Carbon monoxideemission was decreased with increasing limestone. However, the addition of limestone increased the emission of NO[subscript X].